Short Stature Diagnosis and Referral - Maghnie, Mohamad; Labarta, José I.; Koledova, Ekaterina; Rohrer, Tilman R. (Frontiers in Endocrinology, 2018)
The ‘360° GH in Europe’ meeting, which examined various aspects of GH diseases, was held in Lisbon, Portugal, in June 2016. The Merck KGaA (Germany) funded meeting comprised three sessions entitled ‘Short Stature Diagnosis and Referral’, ‘Optimizing Patient Management’ and ‘Managing Transition’. Each session had three speaker presentations, followed by a discussion period, and is reported as a manuscript, authored by the speakers. The first session examined current processes of diagnosis and referral by endocrine specialists for pediatric patients with short stature. Requirements for referral vary widely, by country and by patient characteristics such as age. A balance must be made to ensure eligible patients get referred while healthcare systems are not over-burdened by excessive referrals. Late referral and diagnosis of non-GH deficiency conditions can result in increased morbidity and mortality. The consequent delays in making a diagnosis may compromise the effectiveness of GH treatment. Algorithms for growth monitoring and evaluation of skeletal disproportions can improve identification of non-GH deficiency conditions. Performance and validation of guidelines for diagnosis of GH deficiency have not been sufficiently tested. Provocative tests for investigation of GH deficiency remain equivocal, with insufficient information on variations due to patient characteristics, and cut-off values for definition differ not only by country but also by the assay used. When referring and diagnosing causes of short stature in pediatric patients, clinicians need to rely on many factors, but the most essential is clinical experience.